THE APPLICATION OF PROJECT-BASED LEARNING (PjBL) TO ENHANCE STUDENTS’ CREATIVITY IN POETRY WRITING - Alpin Suhadi; Amor Mardhatillah Aulia; Andrea Rinaldo; Hasmi Suyuthi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study aims to examine the effect of implementing the Project-Based Learning (PjBL) model on students’ creativity in writing poetry. The method used was a quasi-experimental study with a Nonequivalent Control Group Design. This study was conducted at MTsN 2 Aceh Utara. The study population comprised all eighth-grade students, with a sample of 25 students in the experimental class and 25 students in the control class selected through purposive sampling. The experimental class received instruction using the PjBL model, while the control class used conventional teaching methods. Data collection was conducted using a poetry writing creativity assessment rubric covering the aspects of originality, structure, language, and theme. Data were analyzed using an independent t-test with a significance level of 0.05. The analysis results indicated a significant difference in students’ poetry writing creativity between the two classes (t_(calculated) = 6.459, greater than t_(table) = 2.011; p = 0.000, less than 0.05). The average posttest score in the experimental class was 83.24, higher than that of the control class, which scored an average of 71.48. Thus, it can be concluded that the application of the PjBL model is effective in enhancing students’ creativity in writing poetry.